Analysis of the pooled effect of compression ratio and injection timing variation on conventional diesel engine powered with nano doped biodiesel blend - Chinmoy Jit Sarma; Bhaskar Jyoti Medhi; Bhaskor Jyoti Bora; Dilip K. Bora; P. V. Elumalai; Krupakaran Radhakrishnan Lawrence; Debabrata Barik; Ravikumar Ramegowda; Kiran Kavalli; Manzoore Elahi M. Soudagar; Mesay Dejene Altaye (Scientific Reports)
Abstract This research aims to explore how incorporating nanoparticles into a biodiesel-diesel blend influences the performance, combustion, and emission characteristics of a diesel engine under varying conditions, including compression ratios, engine loads, and injection timings. The biodiesel and nanoparticles considered for this investigation are mahua biodiesel and Titanium oxide nanoparticles (TiO2), respectively. The experimental fuel is formulated by blending diesel and mahua biodiesel with the addition of titanium oxide nanoparticles. In this study, compression ratio is varied from 17.5 to 18, whereas fuel injection timing of 20°, 23°, and 25° BTDCs along with engine load variation of 20%, 40%, 60%, 80%, and 100% are considered. The experimentation utilized a single-cylinder diesel engine equipped with a variable compression ratio (VCR) feature and a power output of 3.5 kW. The results indicate that the maximum brake thermal efficiency was achieved at a compression ratio of 18 and a fuel injection timing of 20° before Top Dead Center. For the same setting, the nanoparticle-enriched biodiesel-diesel blend exhibited the lowest levels of CO and HC emissions among all test runs, with reductions of 45.34% and 40%, respectively, compared to standard diesel operation.